The African State in a Changing Global Context: Breakdowns and Transformations - Búr, Gábor (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Búr Gábor a Tarrósy István, Szabó Loránd és Goran Hyden által szerkesztett The African State In A Changing Global Context. Breakdowns And Transformations. című könyvet mutatta be.